EFEKTIVITAS EKSTRAK BIJI PICUNG (Pangium edule Reinw.) TERHADAP MORTALITAS KEONG MAS (Pomacea canaliculate Lamck.) - Yuningsih, Yuningsih; Kartina, Gina (Research Center for Biology-Indonesian Institute of Sciences, 2007)
This research attempted to substitute commercial with botanical molluscicide i.e. picung (Pangium edule) seed. The trial of picung seed water extract (PWE) was conducted in 3 groups of gold apple snails (Pomacea canaliculata) - (GAS).Group 1 with body weight (bw) was 4 to 5 grams, Group 2 was 10 to 12 grams and Group 3 was blank. Both group (1 and 2) were soaked in 4 regimes of cyanide concentration from PWE: 100, 50, 25 and 12.5 /tg/mi and put 10 snails for each concentration. The observation on their mortality was conducted for 24 hours. The result showed that PWE killed 100% of GAS (< 1 hour) with concentration in 50 Âµg/ml and 25 ÃÂµ g/ml cyanide in Group 1 and Group 2, respectively, with clinical sign is the production of excessive mucous as criteria of molluscicide effect thus picung seed is quite significant as botanical molluscicide.